MELACAK SUMBER-SUMBER PENGGUNAAN AYAT-AYAT PENGOBATAN DALAM KITAB SHAMS AL-MA’ĀRIF AL-KUBRĀ - Siti Durrotun Nafisah (STAI AL-ANWAR SARANG, 2019)
This article reveals the sirri knowledge of the work of a scholar 'namely Shaykh al-Būnī entitled Shams al-Ma'ārif al-Kubrā. In this research, the writer uses intertextual theory, which assumes that a text cannot stand alone except with other texts. Al-Būnī himself is known as a Sufi who has a scientific nature from various scholars' to the Prophet. The data of this research show that this book discusses some secret scientific matters, including the secret verses of the Qur’an which can be used as a health treatment for any disease. From the expressions in his book, there is a continuity with several hadiths, the opinions of scholars and other books that become his references. He also have listed several other media besides al-Qur'an which have certain properties which are described by the Al-Qur'an such as the benefits of Misk oil supported by surah al-Fatihah which can be used as medicine. Ibn Qoyyim also explained that the oil itself could be used to facilitate breathing. The conclusion obtained from this study is that the verses of the Qur’an as medication that are listed by al-Būnī in his book are supported by several other books as well as the support of the Qur’an which mentions nutritious ingredients which are also mentioned by al-Būnī in its medication medium. Meanwhile, the verses of the Qur’an listed by al-Būnī for health treatment include surah al-Fātiḥah, al-Ḥashr, al-Burūz, Asmā 'al-A'zām, al-Kahfi, Maryam, and Asmā'ul Ḥusnā.